European Literary Careers : The Author from Antiquity to the Renaissance - De Armas, Frederick A., 1945-; Cheney, Patrick, 1949- (Book collections on Project MUSE., 2002)
In this first book-length study in the fieldof authorial criticism, various specialists from Italian, French, English, and Spanish studies collectively discuss literary careers spanning from classical antiquity through the Renaissance.